A comparison of socioeconomic characteristics that determine the farm income of emerging lifestock and horticultural farmers in South Africa - Moloi, Modise Joshua (My University, 2010)
A large number of emerging farmers in South Africa is involved in subsistence agriculture as a result of poor resource endowment or due to other constraints. Relatively few agricultural products from emerging farmers reach the formal agricultural market. Livestock production is common among emerging farmers and a large proportion of the national livestock is in the hands of the rural poor. Horticultural crops are generally perishable and require immediate disposal, thus implying that the farmers who produce horticultural crops do so with intention to sell their products. Most studies tend to group farmers regardless of their line of production. Only few studies have attempted to investigate the socioeconomic characteristics of farmers, differentiating the commodities that they produce. The objective of this study is to identify and compare the socioeconomic characteristics that determine the farm income of the emerging livestock farmers and horticultural farmers in South Africa. Such an analysis would allow more targeted policy responses for different groups of emerging farmers. The data used in this study consisted of 202 livestock farmers and 126 horticultural farmers selected through quota sample covering all nine provinces in South Africa. The data were collected by the Development Bank of Southern Africa in 2005. Descriptive Analysis and Discriminant Analysis are applied to determine the factors that matter the most in determining incomes of livestock and horticultural farmers. Farm iv income is used as the dependent variable, and fourteen independent variables were identified. The factors that matter the most in determining livestock farmers’ income are, namely access to finance, farm size, age of the household head, membership to farmer organizations and government support. The factors that matter most in determining horticultural farmer’s income are namely farm size, age of the household head, land type (land ownership), and extension services. The results of this study showed that access to land and age of the household head matter the most to both livestock and horticultural farmers. The study found that poor access to land is one of the major constraints facing emerging farmers in South Africa. Land is also one of the factors that may determine the amount of credit the emerging farmers can obtain and, if farmers produce on communal land, it becomes harder to obtain credit. Memberships to farmer’s organisations, government support and access to finance are characteristics that matter the most to livestock and do not seem to matter that much to horticultural farmers. Farmer organisations often lobby for collective provision of appropriate and needed services for their membership. The services that are often lobbied for are services such as extension, marketing and provision of training to empower women and young people so as to enable them to participate fully in farming activities. The results of this study show that there are differences in socio-economic characteristics that matter the most in determining farm income for livestock and horticulture farmers. v Horticulture farmers should be given much support to improve access to get enough land and training while in livestock farming assistance focus should be on access to finance and support services. vi
Thesis (M.Sc. (Agriculture)) --University of Limpopo (Turfloop Campus), 2008
Keywords: Farm income; Horticultural crops; Emerging farmers; Subsistence farming